From ancient pigments to modern optoelectronic applications of arsenic sulfides: bonazziite, the natural analogue of β-As4S4 from Khaidarkan deposit, Kyrgyzstan. (2nd January 2018) - Bindi, Luca; Pratesi, Giovanni; Muniz-Miranda, Maurizio; Zoppi, Matteo; Chelazzi, Laura; Lepore, Giovanni O.; Menchetti, Silvio
Abstract: Bonazziite is a new mineral from Khaidarkan deposit, Kyrgyzstan and represents the natural analogue of the β-form of the well known As4 S4 compound. It occurs as rare crystals up to 100 μm across associated with realgar, sulfur, wakabayashilite, alacránite, non-stoichiometric As4 S4+x sulfides and stibnite in a calcite matrix. In thick section, bonazziite is opaque with a resinous lustre and a dark-orange streak. It is brittle; the Vickers hardness (VHN15 ) is 70 kg/mm 2 (range: 60–76) (Mohs hardness of ∼2½). In plane-polarized incident light, bonazziite is strongly bireflectant and pleochroic from orange to light red. The mineral shows orange to red internal reflections. Between crossed polars, the mineral is strongly anisotropic with greyish to light-blue rotation tints. Reflectance percentages in air for Rmin and Rmax are 19.9, 22.2 (471.1 nm), 19.1, 21.3 (548.3 nm), 18.8, 19.7 (586.6 nm) and 17.8, 18.9 (652.3 nm), respectively. Bonazziite is monoclinic, space group C2/ c, with a = 9.956(1), b = 9.308(1), c = 8.869(1) Å, β = 102.55(2)° and V = 802.3(2) Å 3, Z = 4. The crystal structure [R1 = 0.0263 for 735 reflections with Fo > 4σ(Fo )] is based on the As4 S4 cage-like molecule, in which each As atom links one As and two S atoms. The As4S4 molecule is identical to that found in the structure of realgar. The six strongest powder diffraction lines [ d in Å (I/I0) (hkl) ] are: 5.74 (100) (1̄11); 4.10 (60) (021); 3.92 (50) (1̄12); 3.12 (60) (022, 310); 2.95 (50) (221, 202); 2.86 (80) (2̄22, 1̄31). a mean of six electron microprobe analyses gave the formula As3.95 S4.05, on the basis of eight atoms. The new mineral has been approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (IMA No. 2013-141) and named for Paola Bonazzi, in recognition of her seminal contributions to the study of arsenic sulfides and their alteration induced by exposure to light.